The Influence of Upskilling, Communication Capability and Digital Capability on Employee Performance with Innovation as an Intervening Variable at PT PLN (Persero) Pusmanpro - Pramana, Agus Pawitra Widya; Mujanah, Siti; Ardiana, I Dewa Ketut Raka (International Journal of Economics (IJEC), 2025)
PT PLN (Persero) Project Management Center or called (PLN Pusmanpro) in carrying out its activities managing electricity project management, both power plant projects, transmission, substations and rehabilitation projects, opens opportunities for its employees to innovate in the fields of technology and information systems. The problems that arise in the implementation of the use of the Assignment Monitoring and Reporting System (SIMPP) are that the implementation of this application has been running since 2015 and is still using the old version, then there is no indicator that the use of SIMPP can provide work enthusiasm for employees, because the development of the use of information technology is rapidly changing and increasingly sophisticated, and the level of employee communication and innovation is still relatively poor because there are still limitations to the features in this SIMPP application. The purpose of this study was to determine the effect of upskilling, communication and digital capability on employee performance with innovation as an intervening variable. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of this study were all employees at PLN Pusmanpro. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 126 respondents. The data analysis method uses descriptive analysis and SEM-PLS analysis. The results of the study indicate that the variables of upskilling, communication and digital capability have a positive and significant effect on employee performance through employee innovation at PT PLN Pusmanpro.